2018
DOI: 10.5545/sv-jme.2018.5620
|View full text |Cite
|
Sign up to set email alerts
|

Impact forces occurring in a forced damped multi-body system with clearances

Abstract: The purpose of this paper is to study the effect of clearance and other parameters on the maximal impact forces likely to occur in a forced multi-body system. Numerical simulations are performed for a large range of parameters. The numerical results showed three regions. In the first one, there is no contact between the bodies. The second one, defined as the smooth region, is characterized by regular evolution with a concentration of the impact forces at the boundaries. In the last one, where the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Based on this model, simulations showed that the bypasses strongly modify the behavior of a fuel assembly 23 and of a row of fuel assemblies 24 . The bypasses also have an effect on the structure, creating strong nonlinear effects with impact 25 …”
Section: Introductionmentioning
confidence: 99%
“…Based on this model, simulations showed that the bypasses strongly modify the behavior of a fuel assembly 23 and of a row of fuel assemblies 24 . The bypasses also have an effect on the structure, creating strong nonlinear effects with impact 25 …”
Section: Introductionmentioning
confidence: 99%